A Comparative Study of Static and Dynamic Ball Drill Training on Flick Shooting Performance in Field Hockey - Riskin Nawati; Baiq Satrianingsih; Tiassari Janjang Suminar (Universitas Negeri Semarang, 2026)
The flick is a complex scoring skill in field hockey, and the sequence of its instruction may influence beginner performance. This study examines how training order affects shooting ability in novice players. 24 novice students from the Physical Education, Health, and Recreation program at Universitas Pendidikan Mandalika took part in a quantitative experiment using a pretest–posttest approach. They were divided into two groups. One group practiced flicks starting from a stationary ball before progressing to a moving ball, while the other group trained in the opposite order. Shooting ability was evaluated using the Bobby Charlton shooting test, and the results were analyzed with paired-sample t-tests. Both groups showed clear improvement after the training program (p < 0.05). However, the players who began with moving-ball flick drills improved more and achieved higher final scores than those who started and stationary ball practice. Overall the findings show that both training approaches can help beginners develop flick shooting skills. Still introducing movement earlier in the training seems to give better results. This suggests that not only the type of exercise but also the sequence in which it is taught plays an important role in building technical shooting skills.